Cellulose nanofibril/boron nitride nanosheet composites with enhanced energy density and thermal stability by interfibrillar cross-linking through Ca2+. Issue 4 (29th November 2017) - Yang, Junwei; Xie, Haian; Chen, Hao; Shi, Zhuqun; Wu, Tao; Yang, Quanling; Xiong, Chuanxi
Abstract : Flexible and eco-friendly dielectric materials with high energy density and breakdown strength have promising applications in energy storage devices. Abstract : Flexible and eco-friendly dielectric materials with high energy density and breakdown strength have promising applications in energy storage devices. Here, cellulose nanofibril/boron nitride nanosheet nanocomposite films were fabricated from 2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical (TEMPO)-oxidized cellulose nanofibrils (TOCNs) and hexagonal boron nitride nanosheets (BNNSs) in aqueous dispersions. The obtained TOCN/BNNS nanocomposites were further cross-linked by immersion in aqueous CaCl2 solution to improve their properties. The maximum discharged energy density of the finally prepared composite film was 3.9 J cm −3 with only 4 vol% of BNNSs at 380 MV m −1, achieving greater enhancement than the neat TOCN film with a low energy density of 0.1 J cm −3 at 50 MV m −1 . It is much higher than the previously reported highest energy density of biopolymer-based composites (0.81 J cm −3 ) and also higher than that of the commercially available best dielectric polymer BOPP (2 J cm −3 ). Moreover, the nanocomposite films exhibited excellent mechanical flexibility and significantly improved thermal stability (100 °C increase in thermal decomposition temperature).